THE ROLE OF PRODUCT INNOVATION AND PRODUCT QUALITY ON BUSINESS PERFORMANCE IN MICRO, SMALL AND MEDIUM ENTERPRISES AFFECTED BY THE PANDEMIC - Putra , Ida Bagus Putu Widi; Sujana, Edy; Atmaja, I Made Dwita (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2026)
The existence of a pandemic has disrupted several aspects of the social order. One of them is the economic order which has been greatly affected by the long pandemic. Micro, Small and Medium Enterprises are the economic aspects that are affected, as a result, many businesses choose to go out of business because they are unable to face the crisis. In response to this, the Indonesian government has issued several policies to create a creative economy during the pandemic. But unfortunately, the existence of this policy cannot be responded to properly by business actors. Which in the end causes the business not to develop and even tends to stagnate. For this reason, innovation is deemed necessary to improve the performance of the MSME business in the post-pandemic period because the economy will gradually recover as before. In addition to innovation, it is also necessary to improve product quality following consumer demand and existing trends, so that MSMEs can go hand in hand. This study aims to determine the effect of innovation and product quality improvement on the business performance of Micro, Small and Medium Enterprises. This research is a qualitative descriptive research with the process of collecting data through literature and interviews. The results of this study indicate that innovation on the digital side has no significant effect on the business performance of a business unit. However, improving product quality will help improve business performance in micro, small and medium enterprises during the pandemic and post-pandemic.